2001
DOI: 10.3354/meps218213
|View full text |Cite
|
Sign up to set email alerts
|

Zooplankton feeding behavior and particle selection in natural plankton assemblages containing toxic Alexandrium spp.

Abstract: Laboratory experiments suggest that toxic Alexandrium spp. cells are unpalatable to zooplankton grazers, and that toxic cells should be selectively avoided by zooplankton when feeding in mixtures of different prey species. Such avoidance, if practised in the wild, might contribute to harmful bloom formation by reducing losses of Alexandrium spp. due to grazing. In the spring of 1998 and 1999, during 'red tide' outbreaks in the southwestern Gulf of Maine, weekly experiments were performed using field collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
1
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 45 publications
3
53
1
2
Order By: Relevance
“…However, female Acartia hudsonica from Maine ingest toxic A. fundyense at high rates regardless of whether it is provided as a sole or mixed food (Colin and Dam, 2002b). Similarly, Teegarden et al (2001) found that Acartia hudsonica from Casco Bay, ME fed readily on toxic A. fundyense in natural algal assemblages. Thus, their resistance is not through avoidance of A. fundyense.…”
Section: Effects On Life History Traitsmentioning
confidence: 92%
“…However, female Acartia hudsonica from Maine ingest toxic A. fundyense at high rates regardless of whether it is provided as a sole or mixed food (Colin and Dam, 2002b). Similarly, Teegarden et al (2001) found that Acartia hudsonica from Casco Bay, ME fed readily on toxic A. fundyense in natural algal assemblages. Thus, their resistance is not through avoidance of A. fundyense.…”
Section: Effects On Life History Traitsmentioning
confidence: 92%
“…(Cataletto et al, 1995). The feeding rate of C. finmarchicus increased rapidly with the cell diameter of the algae in the size range 7 to 17 µm (ESD), and ciliates larger than 30 µm were found to be rejected intensively (Teegarden et al, 2001). Although studies on the upper size limit of its food particles were unavailable, phytoplankton as large as 76 µm might be unsuitable for C. sinicus.…”
Section: Discussionmentioning
confidence: 99%
“…Because the defensive function of toxic secondary metabolites in organisms is indisputable, it is often accepted that toxin production has largely evolved to defend prey against predators (e.g., 16,[34][35][36]. Within aquatic systems, there is substantial evidence in support of the evolution of chemical defenses (37,38), and this evidence extends to both macro-and microalgae (13,(39)(40)(41). As such, productive lines of inquiry regarding the function of brevetoxins not only should include how production changes with environmental factors but also must consider the role of biological interactions, especially those between phytoplankton and grazing organisms.…”
Section: Discussionmentioning
confidence: 99%